Intervocalic /t/ acoustic patterns in British news analytical discourse - Androsova, Svetlana V.; Karavaeva, Veronika G. (Penerbit Universiti Kebangsaan Malaysia, 2024)
The paper aims to study word-internal and word-final patterns (allophones, phoneme substitutes and elisions) for intervocalic canonical /t/ in British English. An acoustic analysis of speech samples received from 6 male subjects (1200 intervocalic /t/-tokens, 200 tokens per speaker – 100 medial and 100 final, selected by continuous sampling method from the total of 6 hours of speech) enabled to find three common patterns word-medially (canonical including two-peak ones, taps/flaps, sibilants) and six ones – word-finally (with glottal bursts, weak voiceless and elision added). The results indicate that while word-medial intervocalic glottal burst remains stigmatized, word-final one does not. Neither does it closely correlate with the female gender or young age any more, and it might have become supra-local, supra-gender, and supra-age. Acoustic evidence for both taps and flaps in British English was found. Both of them have continuous voicing, with the first being acoustically closer to stops having a variable duration gap and impulse phase, and the second – closer to approximants demonstrating F-structure, no evidence of occlusion or burst. There was a certain statistically significant speaker-dependent variation in both word-internal and word-final allophones and substitutes. These findings show a high degree of free variation, indicating instability of British Standard Pronunciation. Word-boundary effect was statistically significant for five out of the six subjects. However, the correlation of word-internal and word-final pattern ranks was considerably lower than that between the subjects.